Association of Plasma C1q/TNF-Related Protein 3 (CTRP3) in Patients with Atrial Fibrillation - Liwen Chen; Shuwang Liu; Wei Xu; Yuan Zhang; Jin Bai; Lei Li; Ming Cui; Lijie Sun (Mediators of Inflammation)
Atrial fibrillation (AF) is a highly prevalent cardiac arrhythmia characterized by atrial remodeling. Complement C1q tumor necrosis factor-related protein 3 (CTRP3) is one of the adipokines associated with obesity, diabetes, and coronary heart disease. The association between plasma CTRP3 levels and AF is uncertain. The aim of this study was to investigate whether plasma CTRP3 concentrations were correlated with AF. Our study included 75 AF patients who underwent catheter ablation at our hospital and 47 sinus rhythm patients to determine the difference in plasma CTRP3 concentrations. Blood samples before the ablation were collected, and ELISA was used to measure the concentrations of CTRP3. Plasma CTRP3 concentrations were significantly lower in AF patients compared with control group (366.9±105.2 ng/ml vs. 429.1±100.1 ng/ml, p=0.002). In subgroup studies, patients with persistent AF had lower plasma CTRP3 concentrations than those with paroxysmal AF (328.3±83.3 ng/ml vs. 380.0±109.2 ng/ml, p=0.037). The concentrations of plasma CTRP3 in the recurrence group after radiofrequency catheter ablation of AF were lower than those in the nonrecurrence group (337.9±77.3 ng/ml vs. 386.6±108.1 ng/ml, p=0.045). Multivariate regression analysis revealed the independent correlation between plasma CTRP3 level and AF. Plasma CTRP3 concentrations were correlated with the presence of AF and AF recurrence.